Determinants of Executive Compensation - Albasita Syafna Al'azhary; Suherman Suherman; Agung Dharmawan Buchdadi (Universitas Negeri Gorontalo, 2022)
The object of this research focuses on executive compensation, which is a form of appreciation for the agent’s contribution as the party responsible for the company performance and the improvement of the walfare of the principals. The aims of this study is to determine the effect of profitability and leverage on executive compensation in non financial companies listed in Indonesia Stock Exchange for the period 2017 – 2019. Population of this study is non financial companies listed in Indonesia Stock Exchange for the period 2017 – 2019 with a sample by non financial listed in Kompas100 index to represent the existing population. Independent variables used in this study are profitability which is measured by return on assets (ROA) and leverage which is measured by debt to equity ratio (DER). Dependent variable used in this study is executive compensation which is measured by total remuneration of president director. This study also used control variables such as executive age, executive gender and executive tenure. The sampling method of this study is a purposive sampling. The research model used is panel data with fixed effect model approach. The findings have shown that profitability has a negative significant effect on executive compensation. It is also noted that the lower level of the company’s debt, the larger the amount of executive compensation. These findings shed the light on research on agency theory that compensation on performance is not valid in Indonesia.